ENGLISH TEXTBOOK ANALYSIS “SMART ENGLISH BOOK” GRADE XII SENIOR HIGH SCHOOL BASED ON THE 2013 CURRICULUM AT SMAN 1 MERTOYUDAN - Fauzi, Muhammad Fikar (Faculty of Education and Teachers Training, 2024)
AbstractTo facilitate their teaching and learning processes, every teacher and student requires textbooks. However, not all textbooks released are appropriate for students' needs and have good qualities. This research analyses an English textbook entitled